Dimensi Moral dalam Bentangan Filsafat dan Teori Hukum - Slamet Haryadi (Universitas Bandar Lampung (UBL), 2012)
Expressing justice in law reality will never can penetrate sense of justice because life of construction have by modern life consequence which is materialistis and tend to do not want to strain after, paradigm of Positivism in the form of